Solid state reagent preparation To measure natural radioactivity (Journal of the College of Basic Education, 2022)
In this work, a plastic scintillation detector was prepared using the base material (unsaturated polyester) dissolved in (acetone) and adding different concentrations of the scintillator (anthracene) dissolved in (chloroform), where eight plastic scintillation samples were prepared with a range of (0.1 - 5). g/l) We tested the response of the models to radiation using standard radioactive sources (Cs137, Co60, Am241), where the measurements were made using the counting system. The results of the measurements showed that the detector prepared at a concentration of (4 g / l) was the best among the prepared samples, as its efficiency was about (60-70%) compared to the standard plastic scintillator detector (PW4118)) and also the response of the detector to radiation was good compared to the standard detector.